Condicionamento geologico da agua subterranea em Sao Jose,do Rio Preto, SP. - Barcha, S. F. (My University, 1985)
A study of the geological characteristics of the Buaru Group basaltic substratum and stratigraphical unities was carried out, taking into account the groundwater exploration in S.Jose do Rio Preto area. The presence of the tectonic structures in this substratum exercised a profound influence on the sedimentation of the Bauru Group and on the variations in the hydrological properties of the sediments of the area.-English summary
The geological setting of the groundwater in Sao Jose do Rio Preto, SP, Brazil